Double-network hydrogel containing drug-loaded ACC nanoparticles as well as preparation method and application of double-network hydrogel

By introducing drug-loaded ACC nanoparticles into dual network hydrogels, the problems of loosening of titanium implants and reduced ROS levels in the prior art are solved, and excellent adhesion strength between bone tissue and implants and mitochondrial damage repair are achieved, providing a new bone repair treatment method.

CN119587755AActive Publication Date: 2025-03-11CHONGQING UNIV
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202411808131.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-10
Publication Date
2025-03-11
Estimated Expiration
2044-12-10

AI Technical Summary

Technical Problem

The prior art has shortcomings in reducing loosening of titanium implants and reducing ROS levels at the repair site, resulting in poor adhesion strength between bone tissue and implants and difficulty in effectively repairing mitochondrial damage.

Method used

A dual network hydrogel containing drug-loaded amorphous calcium carbonate (ACC) nanoparticles was used to form a material with excellent adhesion strength and ROS scavenging ability through the combination of LAMG compounds, sodium alginate and ACC nanoparticles.

Benefits of technology

This material can significantly improve the osteogenic differentiation ability of bone marrow mesenchymal stem cells, reduce ROS levels, repair mitochondrial damage, and enhance the adhesion strength of bone tissue to implants, providing a new treatment pathway for bone defects or fracture repair.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119587755A_ABST
    Figure CN119587755A_ABST
Patent Text Reader

Abstract

The invention provides a dual-network hydrogel containing drug-loaded ACC nanoparticles as well as a preparation method and application of the dual-network hydrogel. The double-network hydrogel containing the drug-loaded ACC nanoparticles comprises an LAMG compound, sodium alginate and the drug-loaded ACC nanoparticles, the LAMG compound is prepared by mixing a gelatin aqueous solution and a lipoic acid solution and then carrying out a first reaction, and the drug-loaded ACC nanoparticles are prepared by carrying out a second reaction on a raw material system comprising a nicotinamide mononucleotide aqueous solution, a calcium source solution and ammonium bicarbonate, and mixing the LAMG compound, the sodium alginate and the nano particles containing the drug-loaded ACC, so as to obtain the dual-network hydrogel containing the drug-loaded ACC nano particles. The dual-network hydrogel containing the drug-loaded ACC nanoparticles has excellent adhesion strength and ROS removal capacity, provides a new treatment approach for repair treatment of bone defect or fracture parts, and has important medical significance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of biomedical materials, and in particular to a double network hydrogel containing drug-loaded ACC nanoparticles, and a preparation method and application thereof. Background Art

[0002] Osteoporosis (OP) is a metabolic bone disease with typical characteristics of low bone mass, high bone brittleness, low bone density, bone tissue microstructure damage, and slow bone healing rate. It is common in postmenopausal women, the elderly, and people with nutritional imbalance or deficiency. Studies have shown that the occurrence and development of osteoporosis is related to oxidative stress caused by increased reactive oxygen species (ROS). Higher ROS levels will not only cause oxidative stress behavior in cells such as osteoblasts, osteoclasts, and bone marrow mesenchymal stem cells (BMSCs), reducing cell activity, but will also damage mitochondria in cells and affect the normal metabolic process of cells. With the aging of the population, osteoporosis has become a global health problem. Osteoporosis patients are prone to bone defects or fractures, so there is a high clinical demand for the repair and treatment of bone defects or fractures.

[0003] Clinically, metal implants (bone repair materials) such as bone plates and artificial joints are used to repair bone defects or fractures (repair sites). Among them, titanium implants are widely used in the repair of bone defects or fractures due to their good mechanical and biological properties. Commonly used titanium implant materials include pure titanium, Ti6Al4V, Ti15Zr, etc. Although titanium implants can provide mechanical support, they are prone to loosening.

[0004] In this regard, the prior art usually artificially constructs a transition material on the surface of the titanium implant that has a benign interaction with the bone tissue to reduce the loosening of the titanium implant. For example, the patented technology with publication number CN 104911674 A discloses a bioactive coating on the surface of a porous metal material and a preparation method thereof. The bioactive coating (transition material) is a three-layer structure including a dense film on the metal surface, a porous gel layer in the middle, and a loose layer on the coating surface, which has good adhesion stability. However, the bioactive coating (transition material) still has some problems: (1) The adhesion strength of the bioactive coating to the bone tissue is poor, and the repair site is prone to fall off, affecting the repair effect; (2) The bioactive coating cannot effectively reduce the ROS level at the repair site, and the repair site still has the problem of excessively high ROS levels, making it difficult to repair damaged mitochondria.

[0005] Therefore, exploring a material with both excellent adhesion strength and ROS scavenging ability is a technical problem that needs to be solved urgently in this field. Summary of the invention

[0006] The present invention provides a double network hydrogel containing drug-loaded amorphous calcium carbonate (ACC) nanoparticles. The double network hydrogel containing drug-loaded ACC nanoparticles has excellent adhesion strength and ROS scavenging ability, can reduce ROS levels, effectively repair mitochondrial damage, and can also promote the osteogenic differentiation of bone marrow mesenchymal stem cells (BMSCs), providing a new treatment approach for the repair treatment of bone defects or fractures, and has important medical significance.

[0007] The present invention also provides a method for preparing a double network hydrogel containing drug-loaded ACC nanoparticles, and the method is used to prepare the double network hydrogel having excellent adhesion strength and ROS scavenging ability.

[0008] The present invention also provides a bone repair material, which includes the above-mentioned double-network hydrogel containing drug-loaded ACC nanoparticles and amino-modified titanium, so that the bone repair material has excellent adhesion strength and ROS scavenging ability, and the bone repair material can also promote the osteogenic differentiation of bone marrow mesenchymal stem cells (BMSCs).

[0009] The first aspect of the present invention provides a double network hydrogel containing drug-loaded ACC nanoparticles, comprising a LAMG compound, sodium alginate, and drug-loaded ACC nanoparticles;

[0010] The LAMG compound is formed by a first reaction after mixing a gelatin aqueous solution and a lipoic acid solution, and the drug-loaded ACC nanoparticles are formed by a second reaction of a raw material system including a nicotinamide mononucleotide aqueous solution, a calcium source solution, and ammonium bicarbonate. After the LAMG compound, the sodium alginate and the drug-loaded ACC nanoparticles are mixed, the double-network hydrogel containing the drug-loaded ACC nanoparticles is obtained.

[0011] Gelatin is a well-known biomaterial that is a partial hydrolyzate of natural collagen and has good biocompatibility.

[0012] Lipoic acid is a hydrophobic substance with excellent antioxidant properties that can alleviate cell damage caused by oxidative stress, taurochondriasis, and ferroptosis.

[0013] Nicotinamide mononucleotide (NMN) is a cofactor of nicotinamide adenine dinucleotide (NAD + ), and NAD + It is an important coenzyme of redox reactions and the center of energy metabolism. Its mitochondrial oxidative phosphorylation is an essential process for osteogenic differentiation and bone repair of bone marrow mesenchymal stem cells (BMSCs).

[0014] The inventors have found through extensive research that the double network hydrogel containing drug-loaded ACC nanoparticles (the double network hydrogel containing drug-loaded ACC nanoparticles (GSC) in the embodiment of the present invention) has excellent adhesion strength. The inventors have shown that the double network hydrogel containing drug-loaded ACC nanoparticles can continuously and stably promote the osteogenic differentiation of bone marrow mesenchymal stem cells (BMSCs) at different stages (early, middle and late stages), and the double network hydrogel containing drug-loaded ACC nanoparticles can reduce the ROS level in bone marrow mesenchymal stem cells and effectively repair mitochondrial damage.

[0015] In the present invention, the lipoic acid solution is prepared by mixing lipoic acid with anhydrous ethanol.

[0016] The double network hydrogel containing drug-loaded ACC nanoparticles as described above, wherein the mass ratio of LAMG compound, sodium alginate and drug-loaded ACC nanoparticles is (0.5-2): (0.05-1): (0.005-0.015).

[0017] In some embodiments, in the double network hydrogel, the mass ratio of the LAMG compound, sodium alginate and drug-loaded ACC nanoparticles in the double network hydrogel may preferably be 0.75:0.1:0.0025.

[0018] The double network hydrogel containing drug-loaded ACC nanoparticles as described above, wherein the concentration of gelatin in the gelatin aqueous solution is 0.04 g / mL to 0.07 g / mL;

[0019] and / or, in the lipoic acid solution, the concentration of lipoic acid is 0.01 g / mL to 0.03 g / mL;

[0020] and / or, in the nicotinamide mononucleotide aqueous solution, the concentration of nicotinamide mononucleotide is 11 mg / mL to 15 mg / mL;

[0021] And / or, in the calcium source solution, the concentration of the calcium source is 0.5 mol / L to 2 mol / L.

[0022] The present invention does not specifically limit the mass of gelatin and lipoic acid, and they can be selected according to actual needs. In some embodiments, the mass ratio of gelatin in the gelatin aqueous solution to lipoic acid in the lipoic acid solution is (4-8): (0.8-2).

[0023] The present invention does not impose any particular limitation on the mass of nicotinamide mononucleotide and the volume of the calcium source solution, and they can be selected according to actual needs.

[0024] In the double network hydrogel containing drug-loaded ACC nanoparticles as described above, the calcium source is at least one of calcium chloride, calcium chloride dihydrate, and calcium carbonate.

[0025] The double network hydrogel containing drug-loaded ACC nanoparticles as described above, wherein the temperature of the first reaction is 38° C. to 42° C. and the time is 5 h to 7 h;

[0026] And / or, the temperature of the second reaction is 38° C. to 42° C., and the time is 12 h to 18 h.

[0027] In some embodiments, the temperature of the first reaction may preferably be 40° C. and the time may preferably be 6 hours.

[0028] In some embodiments, the temperature of the second reaction may preferably be 40° C. and the time may preferably be 14 h.

[0029] The second aspect of the present invention provides a method for preparing the double network hydrogel containing drug-loaded ACC nanoparticles, comprising:

[0030] A gelatin aqueous solution and a thioctic acid solution are prepared respectively; the thioctic acid solution is stirred for a first time, and then a catalyst is added and stirred for a second time to obtain a first mixed solution; the gelatin aqueous solution and the first mixed solution are mixed and then reacted for a first time to obtain a first reaction solution; the first reaction solution is dialyzed against distilled water and dried for a first time in sequence to obtain a LAMG compound;

[0031] A nicotinamide mononucleotide aqueous solution is prepared and placed in a reaction container, a calcium source solution is added to the nicotinamide mononucleotide aqueous solution to obtain a mixed solution; anhydrous ethanol is added to the mixed solution to obtain a milky white solution, and then the reaction container is placed in a sealed container with ammonium bicarbonate particles spread on the bottom to obtain a reaction system; the reaction system is subjected to a second reaction to obtain a second reaction liquid; the second reaction liquid is subjected to a first centrifugation treatment, washing, and a second centrifugation treatment in sequence to obtain a precipitate; the precipitate is subjected to a second drying treatment to obtain drug-loaded ACC nanoparticles;

[0032] After mixing the LAMG compound with water, sodium alginate is added, and a second mixed solution is obtained after a third stirring; the drug-loaded ACC nanoparticles are added to the second mixed solution, and a double network hydrogel precursor solution is obtained after a fourth stirring; the double network hydrogel precursor solution is irradiated under ultraviolet light to obtain the double network hydrogel containing drug-loaded ACC nanoparticles.

[0033] The present invention does not specifically limit the reaction container, and the reaction container can be selected according to needs. In some embodiments, the reaction container can be a reaction bottle.

[0034] The present invention does not specifically limit the specific methods of the first drying treatment and the second drying treatment, and can be selected according to actual needs. In some embodiments, the first drying treatment can be freeze-drying treatment at -20°C, and the second drying treatment can be freeze-drying treatment at -20°C.

[0035] In some embodiments, the activated stabilizer is prepared by mixing 1-ethyl-3-[3-dimethylaminopropyl]carbodiimide and N-hydroxysuccinimide.

[0036] The method for preparing the double network hydrogel containing drug-loaded ACC nanoparticles as described above, wherein the first stirring temperature is 35° C. to 38° C. and the time is 25 min to 40 min;

[0037] And / or, the second stirring time is 3 min to 6 min;

[0038] And / or, the temperature of the double distilled water dialysis is 48°C to 52°C and the time is 6d to 8d;

[0039] And / or, the temperature of the first centrifugal treatment is 3°C to 5°C and the rotation speed is 11000rpm to 16000rpm;

[0040] And / or, the temperature of the second centrifugal treatment is 3°C to 5°C, and the rotation speed is 11000 rpm to 16000 rpm.

[0041] The method for preparing the double network hydrogel containing drug-loaded ACC nanoparticles as described above, wherein the third stirring temperature is 48° C. to 52° C. and the time is 2.5 h to 3.5 h;

[0042] And / or, the temperature of the fourth stirring is 38° C. to 42° C., and the time is 10 h to 14 h.

[0043] The third aspect of the present invention provides a bone repair material, comprising the double network hydrogel containing drug-loaded ACC nanoparticles.

[0044] The bone repair material as described above further comprises aminated titanium, and the preparation process of the aminated titanium comprises:

[0045] After the titanium is immersed in nitric acid for the third reaction, a product is obtained. After the product is washed, it is immersed in an APTES ethanol solution for incubation to obtain the amino-modified titanium.

[0046] The present invention does not specifically limit the specific form of titanium. In some embodiments, the titanium can be a titanium sheet, a titanium foil or a titanium rod.

[0047] The bone repair material as described above, wherein the temperature of the third reaction is 58°C to 62°C and the time is 35min to 45min;

[0048] And / or, the incubation temperature is 35°C to 40°C and the incubation time is 1.5h to 2.5h.

[0049] As for the bone repair material mentioned above, the APTES ethanol solution is prepared by adding 3-aminopropyltriethoxysilane into anhydrous ethanol.

[0050] In the bone repair material as described above, the volume ratio of 3-aminopropyltriethoxysilane to anhydrous ethanol is (1-4):(90-120), and the volume ratio of 3-aminopropyltriethoxysilane to anhydrous ethanol may preferably be 2:98.

[0051] In summary, the solution of the present invention has at least the following effects:

[0052] The double network hydrogel containing drug-loaded ACC nanoparticles provided by the present invention comprises a LAMG compound, sodium alginate and drug-loaded ACC nanoparticles; the LAMG compound is formed by a first reaction after mixing a gelatin aqueous solution with a lipoic acid solution, and the drug-loaded ACC nanoparticles are formed by a second reaction of a raw material system including a nicotinamide mononucleotide aqueous solution, a calcium source solution, and ammonium bicarbonate, and the LAMG compound, the sodium alginate and the drug-loaded ACC nanoparticles are mixed to obtain the double network hydrogel containing drug-loaded ACC nanoparticles. Studies have shown that the double network hydrogel containing drug-loaded ACC nanoparticles provided by the present invention has excellent adhesion strength and ROS scavenging ability, can reduce ROS levels, effectively repair mitochondrial damage, and can also promote osteogenic differentiation of bone marrow mesenchymal stem cells (BMSCs), providing a new therapeutic approach for the repair and treatment of bone defects or fractures, and has important medical significance. BRIEF DESCRIPTION OF THE DRAWINGS

[0053] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0054] Figure 1 The morphological characteristics of drug-loaded ACC nanoparticles;

[0055] in, Figure 1 ab are SEM images of drug-loaded ACC nanoparticles; Figure 1cd is the TEM image of drug-loaded ACC nanoparticles; Figure 1 Figure ej is the EDS image of drug-loaded ACC nanoparticles.

[0056] Figure 2 Fourier transform infrared spectrum (FT-IR) of LAMG compounds.

[0057] Figure 3 Scanning electron microscope (SEM) images and atomic force microscope (AFM) images of different titanium materials;

[0058] in, Figure 3 a is a scanning electron microscope (SEM) image of titanium material (Ti), titanium material after nitric acid corrosion treatment (Ti-H), titanium material modified by amino (Ti-NH2) and titanium material modified by double network hydrogel (Ti-GSC); Figure 3 b is an atomic force microscope (AFM) image of titanium material (Ti), amino-modified titanium material (Ti-NH2) and double network hydrogel-modified titanium material (Ti-GSC).

[0059] Figure 4 Adhesion strength test of different hydrogels (Ti-G, NH2-G, NH2-GS, NH2-GSC).

[0060] Figure 5 To detect the early osteogenic differentiation effect of double network hydrogel;

[0061] in, Figure 5 a is the result of quantitative detection of ALP expression level of BMSCs treated in each group at 7 days using ALP activity detection kit; Figure 5 b is a statistical graph showing the quantitative detection of ALP expression levels of BMSCs treated in each group at 7 days using an ALP activity detection kit.

[0062] Figure 6 To test the mid-term osteogenic differentiation effect of double network hydrogel;

[0063] in, Figure 6 a is a result diagram showing the secretion of extracellular collagen (type I collagen) of BMSCs treated in each group on day 14 by Sirius red staining; Figure 6 b is a statistical graph showing the secretion of extracellular collagen (type I collagen) of BMSCs treated in each group at 14 days using Sirius red staining.

[0064] Figure 7 To detect the late osteogenic differentiation effect of double network hydrogel;

[0065] in, Figure 7a is the result of qualitatively and quantitatively detecting the mineralization level of BMSCs treated in each group at 14 days (d) and 21 days (d) by Alizarin red staining; Figure 7 b is a statistical graph of the mineralization levels of BMSCs treated in each group at 14 days and 21 days, which were qualitatively and quantitatively detected by Alizarin red staining.

[0066] Figure 8 To detect the reactive oxygen species (ROS) level of the double network hydrogel;

[0067] in, Figure 8 a is the result of the fluorescence intensity of femoral tissue sections of rats in each group (control group (Ti), Ti-GS group (GS), Ti-GSN group (GSN), Ti-GSC group (GSC)) under a fluorescence microscope; Figure 8 b is a statistical graph of the fluorescence intensity of femoral tissue sections of rats in each group (control group (Ti), Ti-GS group (GS), Ti-GSN group (GSN), Ti-GSC group (GSC)) under a fluorescence microscope. DETAILED DESCRIPTION

[0068] To make the purpose, technical scheme and advantages of the present invention clearer, the technical scheme in the embodiment of the present invention will be clearly and completely described below in conjunction with the embodiments of the present invention. Obviously, the described embodiments are part of the embodiments of the present invention, rather than all of the embodiments. Based on the embodiments in the present invention, all other embodiments obtained by ordinary technicians in the art without making creative work are within the scope of protection of the present invention. If the specific technology or conditions are not indicated in the embodiments, the technology or conditions described in the literature in this area or the product instructions are carried out. The reagents or instruments used that do not indicate the manufacturer are all conventional products that can be obtained commercially.

[0069] The double network hydrogel containing drug-loaded ACC nanoparticles and its preparation method and application provided by the present invention are described in detail below in conjunction with the examples, but they should not be construed as limiting the scope of protection of the present invention.

[0070] Example 1 Drug-loaded ACC nanoparticles and their preparation

[0071] 1. Experimental reagents and materials

[0072] Nicotinamide mononucleotide (NMN), ultrapure water, 1 mol / L calcium chloride solution, anhydrous ethanol, reaction vessel, sealed container.

[0073] 2. Preparation of drug-loaded ACC nanoparticles

[0074] 33.4 mg of nicotinamide mononucleotide (NMN) was added to a reaction bottle containing 2.5 mL of ultrapure water, and the mixture was stirred until NMN was fully dissolved to obtain a nicotinamide mononucleotide (NMN) aqueous solution. 0.5 mL of 1 mol / L calcium chloride solution was added to the NMN aqueous solution, and the mixture was stirred for 5 min to obtain a mixed solution. 40 mL of anhydrous ethanol was added to the mixed solution, and the mixed solution turned milky white. When the laser was irradiated, there was an obvious light path and the Tyndall effect existed to obtain a milky white solution. Then the reaction bottle was placed on the bottom and covered with ammonium bicarbonate particles. to obtain a reaction system; the reaction system was transferred to a heated stirring table at a temperature of 40°C and a rotation speed of 500 rpm to react for 14 hours to obtain a reaction solution; the reaction solution was centrifuged at a temperature of 4°C and a rotation speed of 11000 rpm to obtain a product, the product was washed twice with anhydrous ethanol and then centrifuged at a temperature of 4°C and a rotation speed of 11000 rpm to obtain a precipitate, the precipitate was freeze-dried at -20°C under vacuum conditions to obtain drug-loaded ACC nanoparticles, and stored at 4°C for future use.

[0075] 3. Testing

[0076] (1) Morphological characteristics

[0077] The morphological characteristics of the drug-loaded ACC nanoparticles were observed by scanning electron microscopy (SEM) and transmission electron microscopy (TEM), and the elemental composition of the drug-loaded ACC nanoparticles was determined by TEM's X-ray energy dispersive spectroscopy (EDS).

[0078] SEM results (such as Figure 1 ab) and TEM results (as shown in Figure 1 The EDS results (shown in Figure 2) show that the drug-loaded ACC nanoparticles are uniform in size and spherical in shape, similar to the reported amorphous calcium carbonate (ACC). Figure 1 The data (as shown in ej) showed that NMN-specific elements such as phosphorus (P) and nitrogen (N) were evenly distributed throughout the drug-loaded ACC nanoparticles, and calcium elements specific to calcium carbonate were enriched in the drug-loaded ACC nanoparticles.

[0079] Example 2 Preparation of LAMG Compounds

[0080] 1. Experimental reagents and materials

[0081] Gelatin, ultrapure water, 1 mol / L hydrochloric acid solution, lipoic acid, anhydrous ethanol.

[0082] 2. Preparation of LAMG compounds

[0083] 6 g of gelatin was added to 100 mL of ultrapure water, and stirred at 50° C. until the gelatin was completely dissolved to obtain a gelatin aqueous solution, and a 1 mol / L hydrochloric acid solution was used to adjust the pH of the gelatin aqueous solution to 5.5 to obtain an adjusted gelatin aqueous solution;

[0084] 1.2 g of lipoic acid was added to 60 mL of anhydrous ethanol to obtain a lipoic acid solution, which was then stirred at 37° C. for 30 min until the solution was yellow and transparent, and then 1.0 g of EDC (1-ethyl-3-[3-dimethylaminopropyl]carbodiimide) and 1.0 g of NHS (N-hydroxysuccinimide) were added to the lipoic acid solution and stirred for 5 min to obtain a lipoic acid mixed solution; wherein EDC has the function of activating carboxyl groups, and NHS has the function of maintaining the stability of the activated product after the carboxyl groups are activated;

[0085] At a temperature of 40°C and a rotation speed of 500 rpm, the lipoic acid mixed solution was added dropwise to the adjusted gelatin aqueous solution for mixing. After the addition was completed, the reaction was allowed to react for 6 hours to obtain a reaction solution. The reaction solution was dialyzed against 50°C deionized water for 7 days and then freeze-dried at -20°C under vacuum conditions to obtain a LAMG compound.

[0086] 3. Testing

[0087] (1) Fourier transform infrared spectroscopy (FT-IR)

[0088] Gelatin (Gel), lipoic acid (LA), and LAMG compound (LAMG) were tested by Fourier transform infrared spectrometer reflection method to obtain infrared spectra of gelatin (Gel), lipoic acid (LA), and LAMG compound (LAMG) to analyze the changes in chemical components. The FT-IR results are as follows Figure 3 shown.

[0089] Depend on Figure 2 It can be seen that compared with gelatin (Gel) and lipoic acid (LA), LAMG compound (LAMG) has a peak at 1557 cm -1 The absorption peak at 567 cm is the in-plane bending vibration of the amide bond, indicating that an amidation reaction occurs between LA and Gel. -1 There is a unique disulfide bond (SS) absorption peak belonging to lipoic acid, which proves that lipoic acid is successfully grafted on gelatin.

[0090] Example 3 Preparation of different hydrogels

[0091] 1. Preparation of LAMG hydrogel (G)

[0092] 0.75 g of the above LAMG compound was added to 5 mL of ultrapure water, and stirred at 50° C. and 1000 rpm for 30 min to obtain a LAMG hydrogel precursor solution; the LAMG hydrogel (G) precursor solution was gelled under 365 nm ultraviolet light for 10 min to obtain a LAMG hydrogel (G).

[0093] 2. Preparation of composite hydrogel (GS)

[0094] 0.75 g of the above LAMG compound was added to 5 mL of ultrapure water, stirred at 50° C. and 1000 rpm for 30 min, then 0.1 g of sodium alginate powder was added, and stirred at 50° C. and 50 rpm for 3 h to obtain a composite hydrogel precursor solution; the composite hydrogel (GS) precursor solution was gelled under 365 nm ultraviolet light for 10 min to obtain a composite hydrogel (GS).

[0095] 3. Preparation of NMN-containing hydrogel (GSN)

[0096] 0.75 g of the above-mentioned LAMG compound was added to 5 mL of ultrapure water, stirred at a temperature of 50 ° C and a speed of 1000 rpm for 30 min, and then 0.1 g of sodium alginate powder was added, and stirred at a temperature of 50 ° C and a speed of 50 rpm for 3 h to obtain a mixed solution; NMN was added to the mixed solution, and stirred at a temperature of 40 ° C and a speed of 50 rpm for 12 h to prepare a hydrogel (GSN) precursor solution containing NMN with an NMN content of 0.01 wt%; the hydrogel (GSN) precursor solution containing NMN was gelled under 365 nm ultraviolet light for 10 min to obtain a hydrogel (GSN) containing NMN.

[0097] Preparation of double network hydrogel (GSC) containing drug-loaded ACC nanoparticles

[0098] 0.75 g of the above-mentioned LAMG compound was added to 5 mL of ultrapure water, stirred at a temperature of 50° C. and a rotation speed of 1000 rpm for 30 min, and then 0.1 g of sodium alginate powder was added, and stirred at a temperature of 50° C. and a rotation speed of 50 rpm for 3 h to obtain a mixed solution; 2.5 mg of the above-mentioned drug-loaded ACC nanoparticles was added to the mixed solution, and stirred at a temperature of 40° C. and a rotation speed of 50 rpm for 12 h to prepare a double network hydrogel (GSC) precursor solution containing drug-loaded ACC nanoparticles (content of 0.05 wt%); the double network hydrogel precursor solution was irradiated under ultraviolet light with a wavelength of 365 nm for 10 min to obtain a double network hydrogel containing drug-loaded ACC nanoparticles (double network hydrogel, GSC).

[0099] Example 4 Preparation of different titanium materials

[0100] 1. Experimental reagents and materials

[0101] Pure titanium sheet, ethanol, distilled water, nitric acid, 2wt% APTES ethanol solution.

[0102] 2. Titanium material (Ti)

[0103] The pure titanium sheet was sequentially immersed in ethanol and distilled water for ultrasonic cleaning, and then dried at 60° C. for 6 h to obtain a titanium material (Ti).

[0104] 3. Titanium material after nitric acid corrosion treatment (Ti-H)

[0105] The pure titanium sheet was immersed in ethanol and distilled water for ultrasonic cleaning, and then dried at 60°C for 6 hours. Then, the dried pure titanium sheet was immersed in nitric acid (CAS No.: 7697-37-2) and reacted at 60°C for 40 minutes to obtain a titanium material (Ti-H) after nitric acid corrosion treatment.

[0106] 4. Amide-modified titanium materials (Ti-NH2)

[0107] The pure titanium sheet was soaked in ethanol and distilled water for ultrasonic cleaning, and then dried at 60°C for 6 hours. Then, the dried pure titanium sheet was soaked in nitric acid and reacted at 60°C for 40 minutes. The reacted pure titanium sheet was then placed in a plasma cleaner for cleaning for 5 minutes. After cleaning, it was immediately immersed in a 2wt% APTES ethanol solution (3-aminopropyltriethoxysilane (APTES) was purchased from Shanghai Aladdin Biochemical Technology Co., Ltd., and 2mL APTES was added to 98mL anhydrous ethanol to obtain a 2wt% APTES ethanol solution), and incubated in a shaker at a temperature of 37°C and a rotation speed of 60rpm for 2 hours to obtain an amino-modified titanium material (Ti-NH2).

[0108] 5. Double network hydrogel modified titanium material (Ti-GSC)

[0109] 20 μL of double network hydrogel precursor solution (the same as the double network hydrogel precursor solution prepared in Example 3, the same below) was evenly applied to the surface of the above-mentioned amino-modified titanium material (Ti-NH2), and it was placed under ultraviolet light with a wavelength of 365 nm for 10 minutes to obtain a double network hydrogel-modified titanium material.

[0110] 6. Testing

[0111] (1) Scanning electron microscope (SEM) and atomic force microscope (AFM)

[0112] After the samples were frozen at -80°C, freeze-dried and fixed with liquid nitrogen, they were cut open and the internal structure of the samples was observed using SEM; the changes in the microscopic surface structure of the samples were observed using an atomic force microscope (AFM).

[0113] Titanium material (Ti), titanium material after nitric acid corrosion treatment (Ti-H), titanium material modified by amino (Ti-NH2) and titanium material modified by double network hydrogel (Ti-GSC) were used as samples and tested by scanning electron microscope (SEM) according to the above method. The results are as follows Figure 4 As shown in a; titanium material (Ti), amino-modified titanium material (Ti-NH2) and double network hydrogel-modified titanium material (Ti-GSC) were used as samples for atomic force microscopy (AFM) testing, and the results are shown in Figure 4 As shown in b.

[0114] Depend on Figure 3 From a and b, it can be seen that compared with the surface of titanium material (Ti), the surface roughness of titanium material (Ti-H) and amino-modified titanium material (Ti-NH2) after nitric acid corrosion treatment is significantly increased, but the surface flatness of double network hydrogel-modified titanium material (Ti-GSC) is significantly higher than that of titanium material (Ti) and amino-modified titanium material (Ti-NH2).

[0115] Example 5 Adhesion Strength Test

[0116] 1. Experimental Materials

[0117] Pure titanium foil (1cm*4cm), quartz sheet (1cm*4cm), LAMG hydrogel (G) precursor solution prepared in Example 3, composite hydrogel (GS) precursor solution prepared in Example 3, double network hydrogel (GSC) precursor solution prepared in Example 3.

[0118] 2. Amide-modified titanium foil

[0119] The pure titanium foil (1cm*4cm) was soaked in ethanol and distilled water for ultrasonic cleaning, and then dried at 60°C for 6h. Then, the dried pure titanium foil (1cm*4cm) was soaked in nitric acid and reacted at 60°C for 40min. Subsequently, the reacted pure titanium foil (1cm*4cm) was placed in a plasma cleaner for cleaning for 5min. After cleaning, it was immediately soaked in a 2wt% APTES ethanol solution (the preparation process is the same as above), and incubated in a shaker at 37°C and 60rpm for 2h to obtain amino-modified titanium foil (1cm*4cm).

[0120] 3. Aminated quartz sheet

[0121] The quartz sheet (1cm*4cm) was soaked in ethanol and distilled water for ultrasonic cleaning, and then dried at 60°C for 6h. The dried quartz sheet (1cm*4cm) was then placed in a plasma cleaner for cleaning for 5min. After cleaning, it was immediately soaked in a 2wt% APTES ethanol solution (the preparation process is the same as above), and incubated in a shaker at 37°C and 60rpm for 2h to obtain an amino quartz sheet (1cm*4cm).

[0122] 4. Testing

[0123] (1) 20 μL of LAMG hydrogel (G) precursor solution (consistent with the LAMG hydrogel (G) precursor solution prepared in Example 3, the same below) was dripped onto the upper surface of a pure titanium foil (1 cm*4 cm), and the lower surface of an amino-treated quartz sheet (1 cm*4 cm) was contacted with the LAMG hydrogel (G) precursor solution, and the overlapping area of ​​the titanium foil (1 cm*4 cm) and the amino-treated quartz sheet (1 cm*4 cm) was controlled to be a cube of 1 cm*1 cm and 1.5 mm in thickness, to obtain a test sample (Ti-G), in which the titanium foil (1 cm*4 cm), the LAMG hydrogel (G) precursor solution and the amino-treated quartz sheet (1 cm*4 cm) were stacked in sequence; the test sample (Ti-G) was irradiated under ultraviolet light with a wavelength of 365 nm for 10 min, and then a lap shear test was performed at 37° C. using a universal testing machine at a tensile speed of 0.1 mm / s, and the adhesion strength was calculated.

[0124] (2) 20 μL of LAMG hydrogel (G) precursor solution was dripped onto the upper surface of the above-mentioned amino-modified titanium foil (1 cm*4 cm), and the lower surface of the amino-modified quartz sheet (1 cm*4 cm) was contacted with the LAMG hydrogel (G) precursor solution, and the overlapping area of ​​the amino-modified titanium foil (1 cm*4 cm) and the amino-modified quartz sheet (1 cm*4 cm) was controlled to be a cube of 1 cm*1 cm and 1.5 mm in thickness, to obtain a test sample (NH2-G), in which the amino-modified titanium foil (1 cm*4 cm), the LAMG hydrogel (G) precursor solution and the amino-modified quartz sheet (1 cm*4 cm) were stacked in sequence; the test sample (NH2-G) was irradiated under ultraviolet light with a wavelength of 365 nm for 10 min, and then a lap shear test was performed at 37°C using a universal testing machine at a tensile speed of 0.1 mm / s, and the adhesion strength was calculated.

[0125] (3) 20 μL of a composite hydrogel (GS) precursor solution (the same as the composite hydrogel (GS) precursor solution prepared in Example 3, the same below) was dripped onto the upper surface of the above-mentioned aminated titanium foil (1 cm*4 cm), and the lower surface of the above-mentioned aminated quartz sheet (1 cm*4 cm) was contacted with the composite hydrogel (GS) precursor solution, and the overlapping area of ​​the aminated titanium foil (1 cm*4 cm) and the aminated quartz sheet (1 cm*4 cm) was controlled to be 1 cm*1 cm and the thickness was 1.5 μm. m cube to obtain a test sample (NH2-GS), in which an amino-modified titanium foil (1cm*4cm), a composite hydrogel (GS) precursor solution and an amino-modified quartz sheet (1cm*4cm) are stacked in sequence; the test sample (NH2-GS) is irradiated under ultraviolet light with a wavelength of 365nm for 10min, and then a lap shear test is carried out at 37°C using a universal testing machine at a tensile speed of 0.1mm / s, and the adhesion strength is calculated.

[0126] (4) 20 μL of double network hydrogel (GSC) precursor solution (same as the double network hydrogel (GSC) precursor solution prepared in Example 3, the same below) was dripped onto the upper surface of the above-mentioned amino-modified titanium foil (1 cm*4 cm), and the lower surface of the above-mentioned amino-modified quartz sheet (1 cm*4 cm) was contacted with the double network hydrogel (GSC) precursor solution, and the overlapping area of ​​the amino-modified titanium foil (1 cm*4 cm) and the amino-modified quartz sheet (1 cm*4 cm) was controlled to be 1 cm*1 cm and the thickness was 1.5 μm. m cube to obtain a test sample (NH2-GSC), in which amino-modified titanium foil (1cm*4cm), double-network hydrogel (GSC) precursor solution and amino-modified quartz sheet (1cm*4cm) are stacked in sequence; the test sample (NH2-GSC) is irradiated under ultraviolet light with a wavelength of 365nm for 10min, and then a lap shear test is carried out at 37°C using a universal testing machine at a tensile speed of 0.1mm / s, and the adhesion strength is calculated.

[0127] like Figure 4As shown, compared with the adhesion strength of Ti-G, the adhesion strength of NH2-G is better, which is attributed to the hydrogen bond interaction between the disulfide bond and the amino group and the hydrogen bond interaction between the carboxyl group on the LAMG hydrogel body and the amino group on the surface of the amino-modified titanium foil. The adhesion strength of NH2-GS is better than that of NH2-G, which may be due to the large viscosity of sodium alginate, which improves the adhesion ability of the composite hydrogel (GS) hydrogel. Compared with the adhesion strength of NH2-GS, the adhesion strength of NH2-GSC is higher, indicating that due to the addition of drug-loaded ACC nanoparticles, calcium ions are introduced into the hydrogel system, forming a sodium alginate-calcium hydrogel network with sodium alginate, and forming a double network hydrogel with gelatin, further improving the adhesion strength of the hydrogel. In summary, the double network hydrogel (GSC) provided by the present invention has excellent adhesion strength.

[0128] Example 6 Performance test of double network hydrogel

[0129] 1. Osteogenic differentiation effect detection

[0130] (1) Experimental groups

[0131] There were 4 groups, namely control group (Ti), Ti-GS group (GS), Ti-GSN group (GSN), and Ti-GSC group (GSC);

[0132] Control group (Ti): titanium (Ti) sheet without any treatment;

[0133] Ti-GS group (GS): 20 μL of the composite hydrogel (GS) precursor solution was evenly applied to the surface of an amino-modified titanium sheet (the same as the amino-modified titanium material prepared in Example 4, the same below), and the sheet was irradiated under ultraviolet light with a wavelength of 365 nm for 10 min to obtain a composite hydrogel-modified titanium sheet;

[0134] Ti-GSN group (GSN): 20 μL of NMN-containing hydrogel (GSN) precursor solution was evenly applied to the surface of the amino-modified titanium sheet, and then irradiated under ultraviolet light with a wavelength of 365 nm for 10 min to obtain a NMN-containing hydrogel-modified titanium sheet;

[0135] Ti-GSC group (GSC): 20 μL of double network hydrogel (GSC) precursor solution was evenly applied to the surface of the amino-modified titanium sheet, and it was irradiated under ultraviolet light with a wavelength of 365 nm for 10 min to obtain a double network hydrogel-modified titanium sheet.

[0136] (2) Osteogenic differentiation effect detection

[0137] The titanium sheets of each group (control group, Ti-GS group, Ti-GSN group, Ti-GSC group) were placed in a low-glucose DMEM culture medium (culture medium formula: 4mM L-glutamine, 3700mg / L sodium bicarbonate, 1000mg / L D-glucose 1mM sodium pyruvate) containing 10% FBS in a 24-well plate, and then normal BMSCs (2×104 cells / well) were inoculated for co-culture. The co-culture was carried out for 7 days, 14 days, and 21 days, respectively. The culture medium was replaced every 3 days during this period, and the BMSCs treated in each group (BMSCs treated in the control group, BMSCs treated in the Ti-GS group, BMSCs treated in the Ti-GSN group, and BMSCs treated in the Ti-GSC group) were obtained for the detection of osteogenic differentiation levels at different periods (early, middle, and late).

[0138] ① In order to explore the effects of each treatment group on the early osteogenic differentiation of BMSCs, the alkaline phosphatase (ALP) activity of BMSCs treated in each group was qualitatively detected by alkaline phosphatase (ALP) color reaction on day 7, and the ALP expression level of BMSCs treated in each group was quantitatively detected by ALP activity detection kit on day 7. The results are shown in Table 1. Figure 5 As shown in a and b.

[0139] Previous studies have shown that the higher the ALP expression level of BMSCs in the early stage of osteogenesis, the higher the differentiation potential of BMSCs in the later stage of osteogenesis. Figure 5 The results of a and b showed that the ALP activity of BMSCs treated with Ti-GSC group (GSC) was significantly increased. Compared with BMSCs treated with control group (Ti), the ALP staining of BMSCs treated with Ti-GSC group (GSC) was darker and larger in area. BMSCs treated with Ti-GSN group (GSN) did not show higher ALP expression level than those treated with control group (Ti), which may be because the NMN in GSN had no obvious rescue effect on the osteogenic differentiation of BMSCs in osteoporosis environment, while the ALP expression level of BMSCs treated with Ti-GSC group (GSC) was significantly higher than that of BMSCs treated with Ti-GSN group (GSN), which may be because the introduction of calcium ions in GSC can promote the early osteogenic differentiation of BMSCs.

[0140] ② In order to further explore the effects of each treatment group on the mid-term osteogenic differentiation of BMSCs, Sirius red staining was used to show the secretion of extracellular collagen (type I collagen) of BMSCs treated in each group on day 14. The results are as follows: Figure 6 As shown in a and b.

[0141] Depend on Figure 6The results of a and b showed that compared with BMSCs treated with other groups, the secretion of type I collagen in BMSCs treated with the control group (Ti) was the lowest; the secretion of type I collagen in BMSCs treated with the Ti-GS group (GS) was significantly increased compared with that in the control group (Ti) (P<0.05), which may be because gelatin and sodium alginate, two natural macromolecules, as extracellular matrix (ECM) mimics, provide ECM-like support for BMSCs, stimulating BMSCs to secrete more type I collagen to strengthen ECM formation and remodeling; the secretion of the Ti-GSN group (GSN) was higher than that of the Ti-GS group (GS), which may be due to the fact that the addition of NMN increased the ability of BMSCs to secrete type I collagen in osteoporotic environment by upregulating SIRT1. The secretion of BMSCs treated with the GSC group was the highest, indicating that under the combined action of NMN and calcium ions in the drug-loaded ACC nanoparticles, the secretion of type I collagen in BMSCs was significantly increased, and the effect of promoting the mid-term osteogenic differentiation of BMSCs was significant.

[0142] ③ In order to explore the effects of each group on the late osteogenic differentiation of BMSCs, the mineralization level (absorbance @ 405nm) of BMSCs treated in each group at 14 days (14d) and 21 days (21d) was qualitatively and quantitatively detected by Alizarin red staining and statistically analyzed. The results are as follows: Figure 7 As shown in ac.

[0143] Depend on Figure 7 From the ac, it can be seen that at 14 days, the BMSCs treated with the control group (Ti) showed the lowest mineralization level. The mineralization levels of BMSCs treated with the GS group and the GSN group were improved, which was similar to the results of early osteogenic differentiation detection, indicating that in the presence of two natural macromolecules, gelatin and sodium alginate, osteogenic differentiation can be promoted to a certain extent, while the effect of NMN alone on promoting osteogenic differentiation was not obvious. The mineralization level of BMSCs treated with the GSC group was the highest, which was significantly different from that of other groups, which also showed that the addition of drug-loaded ACC nanoparticles significantly promoted osteogenic differentiation. At 21 days, the mineralization levels of BMSCs treated in each group were further improved compared with those at 14 days, indicating that the osteogenic differentiation level of BMSCs was enhanced with the extension of culture time. The differences between the groups were similar to those at 14 days, but the differences were more significant. As time went on, the BMSCs treated with the GSC group showed a more sustained and stable promotion of osteogenic differentiation of BMSCs.

[0144] 2. Detection of Reactive Oxygen Species (ROS) Levels

[0145] (1) Construction of animal model

[0146] Experimental animals: Female SD rats were purchased from Chongqing Enswell Company.

[0147] Establishment of osteoporosis rat model: Three months after bilateral ovariectomy, 40 rats (n=40) were randomly divided into 4 groups (10 rats in each group) and given the following different treatments:

[0148] Control group (Ti): Titanium (Ti) rods (1.2mm*10mm) without any treatment were used as implants, and then the rats were implanted. The specific process of the implantation surgery is as follows:

[0149] 1) preparing a sodium pentobarbital solution with a concentration of 0.02 g / mL by mixing sodium pentobarbital with pure water;

[0150] 2) The rats were anesthetized by injection of sodium pentobarbital solution (intraperitoneal injection, 0.2 mL / 100 g);

[0151] 3) Place the anesthetized rat on a sterile and clean operating table;

[0152] 4) After using iodine to disinfect the shaved inner and outer sides of the rat's hind legs, a surgical incision was made in the skin at the knee joint using a sterile scalpel, and then the skin layer and muscle layer were carefully cut apart on the outer side of the knee joint (be careful not to scratch the knee joint) and a mark was made on the femoral epiphysis to determine the implantation position;

[0153] 5) Use a surgical electric drill to drill an implantation port (1.2 mm in diameter and 1 cm in length) along the femur, and then implant a titanium (Ti) rod without any treatment;

[0154] 6) Suture the muscle layer and skin layer with absorbable sutures;

[0155] Ti-GS group (GS): 200 μL of composite hydrogel (GS) precursor solution (consistent with the composite hydrogel (GS) precursor solution prepared in Example 3) was perfused into a mold containing an amino-modified titanium rod (1.2 mm*10 mm) (basically the same as the amino-modified titanium material prepared in Example 4, except that: titanium rod (1.2 mm*10 mm), the same below), and then placed under ultraviolet light with a wavelength of 365 nm for cross-linking for 30 min to obtain a GS-treated titanium rod implant, and then the rats were implanted (the specific process of the implantation surgery was basically the same as that of the control group (Ti), except that: the GS-treated titanium rod implant was implanted);

[0156] Ti-GSN group (GSN): 200 μL of NMN-containing hydrogel (GSN) precursor solution (consistent with the NMN-containing hydrogel (GSN) precursor solution prepared in Example 3) was infused into a mold containing an amino-modified titanium rod (1.2 mm*10 mm), and then placed under ultraviolet light with a wavelength of 365 nm for cross-linking for 30 min to obtain a GSN-treated titanium rod implant, and then the rats were implanted (the specific process of the implantation surgery was basically the same as that of the control group (Ti), except that the GSN-treated titanium rod implant was implanted);

[0157] Ti-GSC group (GSC): 200 μL of double network hydrogel (GSC) precursor solution (the same as the double network hydrogel (GSC) precursor solution prepared in Example 3) was poured into a mold containing an amino-modified titanium rod (1.2 mm*10 mm), and then placed under ultraviolet light with a wavelength of 365 nm for cross-linking for 30 minutes to obtain a GSC-treated titanium rod implant, and then the rats underwent implantation surgery (the specific process of the implantation surgery was basically the same as that of the control group (Ti), except that: the GSC-treated titanium rod implant was implanted).

[0158] (2) ROS level detection

[0159] In order to evaluate the level of reactive oxygen species (ROS) in rats of each group, dihydroethidium (DHE) solution was used for fluorescence staining;

[0160] Seven days after the implantation surgery, the rats in each group were intraperitoneally injected with dihydroethidine (DHE) solution (10 μM, 100 μL), and 24 hours after the injection, the rats in each group were killed by intraperitoneal injection of 0.02 g / mL sodium pentobarbital solution (sodium pentobarbital, 200 mg / kg), and the femoral tissues of the rats in each group were collected; the sodium pentobarbital solution was prepared by mixing sodium pentobarbital with pure water;

[0161] The femoral tissues of the rats in each group were decalcified at room temperature for 24 h using a rapid decalcification solution (water: formaldehyde: nitric acid = 750:150:100, 40 mL / rat), and then frozen using OCT (Optimal Cutting Temperature, 4583, Sakura), embedded, and then placed in a liquid nitrogen freezing tank to rapidly freeze the femoral tissues of the rats in each group. Subsequently, femoral tissue sections (thickness of 4 μm) were cut from the rats in each group at -30°C, and the fluorescence intensity of the femoral tissue sections of the rats in each group was observed under a fluorescence microscope, and statistical analysis was performed. The results are shown in FIG. Figure 8 As shown in a and b.

[0162] Depend on Figure 8From a and b, it can be seen that the addition of double network hydrogel (GSC) can greatly improve the problem of excessive ROS around the implant, indicating that GSC itself has excellent ROS scavenging ability. The addition of GSN did not improve ROS scavenging, which may be because the stability of GSN in the body is not high and the mitochondrial damage repair effect is not obvious. The addition of GSC improved the ROS scavenging ability of the implant, which may be because the addition of drug-loaded ACC nanoparticles effectively repaired the mitochondrial damage of bone marrow mesenchymal stem cells around the implant and reduced the ROS level in bone marrow mesenchymal stem cells.

[0163] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein with equivalents. However, these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present invention.

Claims

1. A double network hydrogel containing drug-loaded ACC nanoparticles, characterized in that: Including LAMG compounds, sodium alginate and drug-loaded ACC nanoparticles; The LAMG compound is formed by a first reaction after mixing a gelatin aqueous solution and a lipoic acid solution, and the drug-loaded ACC nanoparticles are formed by a second reaction of a raw material system including a nicotinamide mononucleotide aqueous solution, a calcium source solution, and ammonium bicarbonate. After the LAMG compound, the sodium alginate and the drug-loaded ACC nanoparticles are mixed, the double-network hydrogel containing the drug-loaded ACC nanoparticles is obtained.

2. The double network hydrogel containing drug-loaded ACC nanoparticles according to claim 1, characterized in that: In the double network hydrogel, the mass ratio of the LAMG compound, sodium alginate and drug-loaded ACC nanoparticles is (0.5-2): (0.05-1): (0.005-0.015).

3. The double network hydrogel containing drug-loaded ACC nanoparticles according to claim 1, characterized in that: In the gelatin aqueous solution, the concentration of gelatin is 0.04 g / mL to 0.07 g / mL; and / or, in the lipoic acid solution, the concentration of lipoic acid is 0.01 g / mL to 0.03 g / mL; and / or, in the nicotinamide mononucleotide aqueous solution, the concentration of nicotinamide mononucleotide is 11 mg / mL to 15 mg / mL; And / or, in the calcium source solution, the concentration of the calcium source is 0.5 mol / L to 2 mol / L.

4. The double network hydrogel containing drug-loaded ACC nanoparticles according to claim 3, characterized in that: The calcium source is at least one of calcium chloride, calcium chloride dihydrate and calcium carbonate.

5. The double network hydrogel containing drug-loaded ACC nanoparticles according to claim 1, characterized in that: The temperature of the first reaction is 38°C to 42°C and the time is 5h to 7h; And / or, the temperature of the second reaction is 38° C. to 42° C., and the time is 12 h to 18 h.

6. A method for preparing a double network hydrogel containing drug-loaded ACC nanoparticles according to any one of claims 1 to 5, characterized in that: include: Separately preparing a gelatin aqueous solution and a lipoic acid solution; After the lipoic acid solution is first stirred, an activated stabilizer is added and then a second stirring is performed to obtain a first mixed solution; The gelatin aqueous solution is mixed with the first mixed solution and then subjected to a first reaction to obtain a first reaction solution; the first reaction solution is dialyzed against distilled water and subjected to a first drying treatment to obtain a LAMG compound; A nicotinamide mononucleotide aqueous solution is prepared and placed in a reaction container, a calcium source solution is added to the nicotinamide mononucleotide aqueous solution to obtain a mixed solution; anhydrous ethanol is added to the mixed solution to obtain a milky white solution, and then the reaction container is placed in a sealed container with ammonium bicarbonate particles spread on the bottom to obtain a reaction system; the reaction system is subjected to a second reaction to obtain a second reaction liquid; the second reaction liquid is subjected to a first centrifugation treatment, washing, and a second centrifugation treatment in sequence to obtain a precipitate; the precipitate is subjected to a second drying treatment to obtain drug-loaded ACC nanoparticles; After mixing the LAMG compound with water, sodium alginate is added, and a second mixed solution is obtained after a third stirring; the drug-loaded ACC nanoparticles are added to the second mixed solution, and a double network hydrogel precursor solution is obtained after a fourth stirring; The double network hydrogel precursor solution is irradiated under ultraviolet light to obtain the double network hydrogel containing drug-loaded ACC nanoparticles.

7. The double network hydrogel containing drug-loaded ACC nanoparticles according to claim 6, characterized in that: The first stirring temperature is 35°C to 38°C and the time is 25min to 40min; And / or, the second stirring time is 3 min to 6 min; And / or, the temperature of the double distilled water dialysis is 48°C to 52°C and the time is 6d to 8d; And / or, the temperature of the first centrifugal treatment is 3°C to 5°C and the rotation speed is 11000rpm to 16000rpm; And / or, the temperature of the second centrifugal treatment is 3°C to 5°C, and the rotation speed is 11000 rpm to 16000 rpm.

8. The double network hydrogel containing drug-loaded ACC nanoparticles according to claim 6, characterized in that: The third stirring temperature is 48°C to 52°C and the time is 2.5h to 3.5h; And / or, the temperature of the fourth stirring is 38° C. to 42° C., and the time is 10 h to 14 h.

9. A bone repair material, characterized in that: The invention comprises the double network hydrogel containing drug-loaded ACC nanoparticles as claimed in any one of claims 1 to 5.

10. The bone repair material according to claim 9, characterized in that: Also included is aminated titanium, the preparation process of which includes: After the titanium is immersed in nitric acid for the third reaction, a product is obtained. After the product is washed, it is immersed in an APTES ethanol solution for incubation to obtain the amino-modified titanium.

Citation Information

Patent Citations

  • Bioactive coating on surface of porous metal material and preparation method of bioactive coating

    CN104911674A

  • Therapeutic molecules

    CA2514071A1

  • Apparatuses, methods, and compositions for the treatment and prophylaxis of chronic wounds

    CN103402556A

  • Hydroxyapatite nanoparticles entrapped with beta-nicotinamide mononucleotide as well as preparation method and application of hydroxyapatite nanoparticles

    CN116637120A